Pengaruh Kompetensi, Motivasi, Kompensasi terhadap Kinerja Pegawai di PT. XYZ Ciputat Timur - Eva Aihulia (Warta Pendidikan | e-Journal, 2022)
This objective of this research is to examine the influence of competency, motivation and compensation to the performance in the PT. XYZ Ciputat Timur. The research is causality using survey approach. Data was collected by distributing questionnaires to all employee servants who employee performance in the PT. XYZ as 40 people. Methods of data analysis using descriptive statistical analysis, classic assumption testing, validity and reliability testing and hypothesis testing by multiple regression analysis techniques were processed using by SPSS for Windows programs. Based on the results of testing the coefficient of determination resulted in adjusted R-Square of 0,839 or 83,9 %, demonstrating the influence of variable competency, motivation, compensation and work environment to the employee performance, where as 16,1 % are affected by other factors not examined in this research variables or other factors that have not been studied in this study such as work culture, incentives, leadership style, etc. These results showed that: (1) Simultaneously, competency, motivation and compensation to the performance have a effect to the performance in thePT. XYZ; and (2) Partially, competency, motivation and compensation to the performance have a effect to the performance in the PT. XYZ.